1996
DOI: 10.1139/m96-134
|View full text |Cite
|
Sign up to set email alerts
|

Water and temperature relations and microconidial germination of Fusarium moniliforme and Fusarium proliferatum from maize

Abstract: The effects of water activity (aW, 0.994-0.85 = 0.4-21.0 (-)MPa water potential), temperature (5-42 degrees C), and their interactions on microconidial germination of three isolates each of Fusarium moniliforme and Fusarium proliferatum were determined in vitro on a maize meal extract medium. Temporal germination rates of microconidia of isolates of both species were significantly influenced by both aW and temperature. Germination was very rapid at > 0.94 aW with an almost linear increase with time. Germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 19 publications
4
49
1
Order By: Relevance
“…The average diameter of each growing mycelial colony was measured daily in two perpendicular directions (Marín et al, 1996;Lahlali et al, 2005) without opening the Petri dishes.…”
Section: Growth Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The average diameter of each growing mycelial colony was measured daily in two perpendicular directions (Marín et al, 1996;Lahlali et al, 2005) without opening the Petri dishes.…”
Section: Growth Measurementmentioning
confidence: 99%
“…Nevertheless, most of the models derive from models based on bacterial data due to the inherent difficulties in assessment of fungal growth rates and gathering of sufficient suitable and reproducible data (Gibson and Hocking, 1997;Dantigny et al, 2005a). Various workers have developed probability, mechanistic/semi-mechanistic, empirical and thermal death models for a variety of toxigenic and spoilage fungi (Pitt, 1993;Skirdal and Eklund, 1993;Gibson et al, 1994;Marín et al, 1996;Cuppers et al, 1997;El-Halouat and Debevere, 1997;Valík and Piecková, 2001;Sautour et al, 2002). The major objective of the present work was to construct and evaluate models describing the individual and combined effects of water activity and temperature on the radial growth rate of B. cinerea for each tested solute.…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of water content in media was checked by a w measurement of inoculated Petri dishes after 25 days at each temperature. The radius of each growing mycelial colony was measured daily in two directions at right angles to each other (Marin et al, 1996) without opening the Petri dishes. Three replicates were used per solute-a w -temperature combination.…”
Section: Preparation Of the Mycelium Inoculummentioning
confidence: 99%
“…Marín et al (1996) found that the aw minima for the microconidial germination of Spanish isolates of F. moniliforme and F. proliferatum were 0.88 on maize meal extract medium. (Marín et al, 1996;Etcheverry et al, 2002).…”
Section: Germinationmentioning
confidence: 95%
“…Marín et al (1996) found that the aw minima for the microconidial germination of Spanish isolates of F. moniliforme and F. proliferatum were 0.88 on maize meal extract medium. (Marín et al, 1996;Etcheverry et al, 2002). Earlier, Francis and Burgess (1977) found that the percentage germination of conidia, ascospores and chlamydospores of F. graminearum Group II isolates was reduced as water potential was lowered from −1 to −20 bars.…”
Section: Germinationmentioning
confidence: 95%